2018
DOI: 10.1002/gepi.22179
|View full text |Cite
|
Sign up to set email alerts
|

A novel association of rs13334070 in the RPGRIP1L gene with adiposity factors discovered by joint linkage and linkage disequilibrium analysis in Iranian pedigrees: Tehran Cardiometabolic Genetic Study (TCGS)

Abstract: Understanding the genetic and metabolic bases of obesity is helpful in planning and developing health strategies. Therefore, the first family‐based joint linkage and linkage disequilibrium study was conducted in Iranian pedigrees to assess the relationship between obesity and single‐nucleotide polymorphisms (SNPs) located in the 16q12.2 region. In the present study, a total of 13,344 individuals were included, of whom 12,502 individuals were within 3,109 pedigrees and 842 were unrelated singletons. To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…To increase the association test's power and accommodate the epistasis effect between adjacent correlated SNPs in a set, we used a logistic kernel machine regression method to assess SNP sets' association binary phenotype 23 , 28 , 49 , 50 . In the additive model, genotypes AA, Aa, and aa recoded to 0, 1, and 2, respectively 28 , 50 .…”
Section: Methodsmentioning
confidence: 99%
“…To increase the association test's power and accommodate the epistasis effect between adjacent correlated SNPs in a set, we used a logistic kernel machine regression method to assess SNP sets' association binary phenotype 23 , 28 , 49 , 50 . In the additive model, genotypes AA, Aa, and aa recoded to 0, 1, and 2, respectively 28 , 50 .…”
Section: Methodsmentioning
confidence: 99%
“…As the rst comprehensive study on Iranian pedigrees, we conducted a family-based joint linkage and linkage disequilibrium analysis of 3109 pedigrees. We found that RPGRIP1L is the key gene within the 16q12.2 region whose polymorphisms could be associated with obesity risk factors among TCGS participants [24]. Moreover, different SNP clusters composed of rare and common SNPs within the 16q12.2 region signi cantly increased BMI among Iranians.…”
Section: Resultsmentioning
confidence: 78%
“…Recently, mutations in RPGRIP1L were reported in obesity and brain function. One study showed that rs13334070, in RPGRIP1L intron 4, has a significant association with obesity (Javanrouh et al, 2019). Reble et al recently identified a SNV, rs7203525, that influences an alternative splicing event in RPGRIP1L, increasing exon 20 inclusion and potentially impacting brain function (Reble et al, 2020).…”
Section: Discussionmentioning
confidence: 99%